Manajemen Komunikasi Orang Tua dalam Meningkatkan Prestasi Anak Usia Dini (AUD) (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
Early childhood achievement can be said to have declined, this is due to the lack of communication management of parents towards children. Achievement is something that needs to be developed, especially in the age range of 0-6 years (early childhood). Based on research conducted by the author, the main way that parents can develop or improve children's achievement is through parental communication management. The application of communication management can be done without cornering the interlocutor.